Kehendak dan kepuasan pelanggan IPTA terhadap perkhidmatan telekomunikasi Maxis - Zainol Mustafa,; Nur Riza Mohd Suradi,; Wan Norsiah Mohamed,; Zalina Mohd Ali,; Faridatulazna Ahmad Shahabuddin,; Chai , Chun Fatt; Juwairiyah Mohd Ali , (Penerbit ukm, 2008)

(untitled)
This study examined the customer satisfaction on Maxis Services using Importance- Performance Analysis (IPA) and Penalty Rewards Contrast Analysis. 325 respondents from public higher education institution (PHEI) students were selected randomly. The instrument of this study is questionnaire that contains seven factors for analysis including service cost, network coverage, network promotion, customer counter services, website customer services, operator services and other services. This study observed the level of importance and satisfaction of customers on the attributes stated using 1 to 7 Likert’s scale. The result shows that there are some factors that need more emphasis and improvements to achieve customer’s satisfaction and hence increase Maxis quality of services in Malaysia